The Colonial Roots of Criminal Procedure in the Philippines - Rossabi, Amy (Columbia Journal of Asian Law, 1997)
Centuries of colonial rule profoundly influenced Filipino social, political, and legal institutions. Filipino law, in particular, evolved as a synthesis of indigenous, Spanish (Roman), and American common laws, each building on its forerunner to create a system unique to the Philippines. As a succession of alien powers colonized the Philippines, they preserved some of the existing laws, altering only those in conflict with their own and adding a few to encompass new commercial, political, or religious conditions. When the Spanish established a colonial government in 1565, they initially permitted the native inhabitants to continue with many of their indigenous customs instead of imposing their own traditions derived from the Roman legal code. As they became more entrenched, however, the Spanish attempted to subvert many of the customary laws. American officials, who displaced the Spanish in 1898, generally adopted the same policy by incorporating certain features of Roman law while simultaneously tolerating some of the remaining native legal traditions. The Americans thus drew on much of the existing substantive law but also found that the Spanish had failed to introduce laws of procedure to the archipelago. Moreover, the few procedural measures that the Spanish brought with them appeared to be inconsistent with American concepts of justice. Within two years of their arrival, U.S. colonial officials issued General Orders No. 58, which instituted a code of criminal procedure that was more consonant With American legal ideals. The code of criminal procedure the American colonials introduced in 1900, remains virtually unchanged in 1997 and governs present-day criminal procedure in the Philippines. Thus procedural reforms of the colonial past had a tremendous impact on the current Filipino legal system.